TAX ACCOUNTING ANALYSIS ON ELECTRONIC FINANCIAL PRODUCTS IN INDONESIA - Oktavia Oktavia (FEBI UIN Sunan Gunung Djati Bandung, 2023)
Accounting is based on the capacity to describe in numbers the numerous financial activities of a firm, which has to be taken into consideration whenever decisions are being made about that company. The administration of taxes is an essential component in the growth of Indonesia. Because of the advent of new financial products that help improve taxpayer declarations and, as a consequence, the economy of the nation, this sort of accounting has had a significant expansion in recent years. This is a digital version of a traditional financial product. The overarching objective of this research is to investigate tax accounting methods that are based on electronic financial instruments. This research takes both a qualitative and a descriptive approach to data collection and analysis. Our results are predicated on the utilization of electronic financial products as well as the reality of tax accounting that is based on electronic financial product data. It was determined that these electronic documents, such as electronic invoices, contribute to the promotion and development of a new tax culture that facilitates the growth of countries by making their accounting and declarations much simpler and more accessible. This new tax culture is beneficial to the growth of countries because it allows countries to more easily keep track of their financial transactions.